Role of catecholate siderophores in gram-negative bacterial colonization of the mouse gut - Pi, Hualiang; Jones, Shari A.; Mercer, Lynn E.; Meador, Jessica P.; Caughron, Joyce E.; Jordan, Lorne; Newton, Salete M.; Conway, Tyrrell; Klebba, Phillip E. (My University, 2012)
We investigated the importance of the production of catecholate siderophores, and the utilization of their iron (III) complexes, to colonization of the mouse intestinal tract by Escherichia coli. First, a ΔtonB strain was completely unable to colonize mice. Next, we compared wild type E. coli MG1655 to its derivatives carrying site-directed mutations of genes for enterobactin synthesis (ΔentA::Cm; strain CAT0), ferric catecholate transport (Δfiu, ΔfepA, Δcir, ΔfecA::Cm; CAT4), or both (Δfiu, ΔfepA, ΔfecA, Δcir, ΔentA::Cm; CAT40) during colonization of the mouse gut. Competitions between wild type and mutant strains over a 2-week period in vivo showed impairment of all the genetically engineered bacteria relative to MG1655. CAT0, CAT4 and CAT40 colonized mice 10[superscript 1]-, 10[superscript 5]-, and 10[superscript 2]-fold less efficiently, respectively, than MG1655. Unexpectedly, the additional inability of CAT40 to synthesize enterobactin resulted in a 1000-fold better colonization efficiency relative to CAT4. Analyses of gut mucus showed that CAT4 hyperexcreted enterobactin in vivo, effectively rendering the catecholate transport-deficient strain iron-starved. The results demonstrate that, contrary to prior reports, iron acquisition via catecholate siderophores plays a fundamental role in bacterial colonization of the murine intestinal tract.
Keywords: Catecholate siderophores; Mouse intestinal tract; Escherichia coli; Bacterial colonization